A standardized extract of Rhynchosia volubilis Lour. exerts a protective effect on benzalkonium chloride-induced mouse dry eye model. (6th April 2018) - Kang, Suk Woo; Kim, Kyung-A.; Lee, Chung Hyun; Yang, Sung Jae; Kang, Tae Kyeom; Jung, Je Hyeong; Kim, Tae-Jin; Oh, Sang-Rok; Jung, Sang Hoon
Abstract: Ethnopharmacological relevance: In contrast to other leguminous plants generally used as food, Rhynchosia volubilis Loureiro, a small soybean with a black seed coat, has been used as a traditional oriental remedy for various human diseases in Eastern Asia. In this study, we demonstrated the protective effect of R. volubilis against dry eye disease. Aim of the study: We aimed to investigate whether a standardized ethanol extract of R. volubilis (EERV) can protect the cornea in a benzalkonium chloride (BAC)-induced mouse dry eye model. Materials and methods: Experimental dry eye was induced by the instillation of 0.2% BAC on mouse cornea. A standardized ethanol extract of R. volubilis (EERV) was orally administered following BAC treatment. The positive control group was treated with commercial eye drops. Fluorescein staining, tear break-up time (BUT), and hematoxylin and eosin staining were evaluated on the ocular surface. Squamous metaplasia and apoptosis in the corneal epithelial layer were detected by immunostaining. Furthermore, the protein expression of cytochrome c, Bcl-2, and Bax was determined. Results: EERV treatment significantly improved fluorescein scoring, BUT, and smoothness in the cornea compared to the vehicle group. In addition, EERV inhibited squamous metaplasia and apoptosis in the cornea. The expression of cytochrome c and Bax was upregulated, while that of Bcl-2 was downregulated in the vehicle group compared with that in the control group. However, EERV treatment inhibited the expression of cytochrome c and Bax, while that of Bcl-2 was improved. Conclusion: Standardized EERV could be a beneficial candidate for the treatment of dry eye disease. Graphical abstract: fx1